Estimating the global trade in Southeast Asian newts. (July 2016) - Rowley, Jodi J.L.; Shepherd, Chris R.; Stuart, Bryan L.; Nguyen, Truong Q.; Hoang, Huy D.; Cutajar, Timothy P.; Wogan, Guinevere O.U.; Phimmachak, Sompouthone
Abstract: The global trade in amphibians is widespread, involves hundreds of species, and has been implicated in amphibian population declines. The pet trade is the primary driver for population declines in one Southeast Asian newt species ( Laotriton laoensis ), and is a known threat to most of the 13 other known species from the region. Despite this, there has been little attempt to assess the impact of collection for the pet trade on Southeast Asian newts. We examined available import data from the US, Europe and Hong Kong, assessed current online trade and surveyed local pet traders within Southeast Asia. Large numbers of Southeast Asian newts are harvested from the wild to meet the demands of the international pet trade, with more than 7500 individual newts imported into the US alone during 2005–2014. Internet trade surveys revealed the global extent of the trade, with Southeast Asian newts for sale as pets in 15 countries throughout Europe, Asia and North America, at between USD30–260 each. The trade in newts within Southeast Asia appears negligible in comparison. Urgent measures are required in order to conserve Southeast Asian newts but the lack of data on the species and number of individuals impacted by the pet trade makes it difficult to monitor and accurately assess its threat. We strongly recommend that all Southeast Asian newts be listed on CITES. This measure should improve monitoring of trade and provides importing countries opportunity to curb trade in species that were illegally harvested, thus helping to safeguard wild populations. Graphical abstract: Highlights: The pet trade is a threat to Southeast Asian newt species, but is poorly understood. The limited import data available revealed substantial trade in Southeast Asian newts. Internet surveys revealed Southeast Asian newts for sale as pets in 15 countries. We recommend that all Southeast Asian newts should be listed in CITES.